(untitled) (Global Journal of Medical Research, 2020)
PD-L1 signaling is essential in regulating T cell function and keeping the balance of tumor microenvironment, but its role in modifying TCR-T cell cytotoxicity remains unknown. MART-1-specific TCR-T cells (TCR-T MART-1 ) were stimulated by MEL-526 tumor cells expressing different proportions of PD-L1 and used to perform cytotoxicity assays and single-cell RNA sequencing. Percentage changes of different specific cell clusters were analyzed. The percentage of cluster HLA-DR + CD38 + CD8 + was upregulated after antigen stimulation, and tumor PD-L1 modified TCR-T cell function through downregulating the percentages of HLA-DR + CD28 + CD8 + and HLA-DR + CD38 + CD8 + subsets which were higher in TCR-T MART-1 than in T null .